Efficacy and safety of 4% articaine with epinephrine for the anterior middle superior alveolar nerve block comparing to the computer-controlled and conventional anesthetic delivery: prospective, randomized, cross-over clinical study - Ćetković, Dejan; Milić, Marija S.; Biočanin, Vladimir; Brajić, Ivana; Ćalasan, Dejan; Radović, Katarina; Živković, Rade; Brković, Božidar (Vojnosanitetski pregled, 2021)
Abstract Bacground/Aim. The efficient dental anesthesia, which is related to the clinically adequate depth, duration and the width of anesthetic field, is an important prerequisite for successful dental treatment. The aim of this study was to investigate and compare the pulpal anesthesia and cardiovascular parameters after the anterior middle superior alveolar (AMSA) nerve block with 4% articaine with epinephrine administered by conventional cartridge-syringe and computer-controlled local anesthetic delivery system (CCLADS). Methods. This controlled double-blind cross-over randomized clinical study included 38 healthy volunteers. Efficacy of pulpal anesthesia after the AMSA nerve block was evaluated by measuring a success rate, onset and duration of pulpal anesthesia, using an electrical pulp tester. The parameters of cardiovascular function (systolic and diastolic blood pressure, heart rate) were monitored noninvasively. Results. Successful pulpal anesthesia of all tested teeth was obtained in 57.9% participants with CCLADS and in 44.7% participants with conventional syringe. The onset time was not significantly different between two investigated groups. The pulpal anesthesia duration was not significantly different neither within nor between investigated groups. The systolic and diastolic blood pressures were significantly decreased in both investigated groups, in comparison with the baseline values. Heart rate significantly decreased within CCLADS from 10th to 30th minute when compared to baseline. Conclusion. The efficacy of pulpal anesthesia and safety of cardiovascular profile of 0.6 mL of articaine with epinephrine (1:100.000) delivered with CCLADS were improved in comparison to the conventional syringe delivery. Significant changes of cardiovascular function were not observed.